2009
DOI: 10.4314/ajep.v16i1.48822
|View full text |Cite
|
Sign up to set email alerts
|

Capital flight and its determinants in the Franc zone

Abstract: List of tables 1. Currency composition of the FZ countries' long-term debt in various currencies (%) 2. Total real capital flight in the FZ (million 2000 $ US, % of GDP and % of external debt), 1970-2005 a 18 3. Descriptive statistics 4. Correlation coefficients 5. Determinants of capital flight in the FZ (World Bank method #) 6. Determinants of capital flight in the FZ (Morgan Guaranty method #) A.1. Macroeconomic performances in the FZ and in non-FZ (in %) A.2. Empirical studies on the determinants of capita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 49 publications
2
28
0
Order By: Relevance
“…The main variables that have been identified as determinants of capital flight are past capital flight, external debt, foreign aid, foreign direct investment, high inflation, low economic growth, deterioration of the terms of trade, higher budget deficit, the tax system, exchange rate overvaluation, interest rate differentials, demand deposits, credit to the private sector, total liquid liabilities (M3), governance and institutional quality, political risks and war, and the uncertainty of public policies. For more detailed information, see Ndikumana and Boyce (), Ndiaye (), and Ndikumana et al . ().…”
Section: The Literaturementioning
confidence: 99%
“…The main variables that have been identified as determinants of capital flight are past capital flight, external debt, foreign aid, foreign direct investment, high inflation, low economic growth, deterioration of the terms of trade, higher budget deficit, the tax system, exchange rate overvaluation, interest rate differentials, demand deposits, credit to the private sector, total liquid liabilities (M3), governance and institutional quality, political risks and war, and the uncertainty of public policies. For more detailed information, see Ndikumana and Boyce (), Ndiaye (), and Ndikumana et al . ().…”
Section: The Literaturementioning
confidence: 99%
“…The model specification and estimation draw on the existing empirical literature. We specifically allow for the persistence of capital flight over time and the revolving door phenomenon, whereby some fraction of external borrowing fuels capital flight, in a dynamic formulation of the econometric model (Ndiaye, 2009;Boyce, 2003, 2011b). The estimation equation is therefore specified as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Even though the results vary, due in part to differences in the measurements of capital flight used, the countries considered, the econometric techniques, and the models employed, some important empirical regularities can be pointed out. Most of the studies focusing on African countries identified macroeconomic and political conditions as important factors of capital flight (Lensink et al ., ; Collier et al ., ; Ndikumana and Boyce, ; Ndiaye, ; Vespignani, ; Cerra et al ., ). More specifically, the list of determinants includes past capital flight, capital inflows, and capital stock (measured by debt inflows, debt stock, and aid flows), macroeconomic instability (measured by exchange rate overvaluation, government deficits, the inflation rate, and current account deficits), rate of return differentials, financial development, governance and institutional quality, political risks and war, and the uncertainty of public policies (measured by government consumption expenditures, taxes, budget deficits, and real interest rates) (Ajayi, ; Ng'eno, ; Olopoenia, ; Hermes and Lensink, ; Hermes et al ., ; Cerra et al ., ; Ndikumana and Boyce, , ; Ajayi, ; Ndiaye, ; Le and Rishi, ).…”
Section: Econometric Analysis Of the Determinants Of Capital Flightmentioning
confidence: 98%
“…Thus, as outlined in empirical findings by Boyce and Ndikumana (), among others, who have focused on other countries, the growing foreign debt of Ethiopia may increase expectations about exchange rate depreciation and higher taxation, which provides a stimulus to hold foreign assets and hence capital flight. Capital flight also forces governments to borrow to bridge the resulting financing gap, which further increases the debt burden and worsens the fiscal balance that in turn triggers capital flight (see also Cuddington, ; Hermes and Lensink, ; Boyce, ; Ndikumana, ; Ndikumana and Boyce, ; Ndikumana and Boyce, , ; Ndiaye, ). External debt flows also make foreign exchange directly available to the country.…”
Section: Econometric Analysis Of the Determinants Of Capital Flightmentioning
confidence: 99%